2009
DOI: 10.1002/per.728
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of GMA to counterproductive work behavior revisited

Abstract: Recent research reported that general mental ability (GMA) predicted counterproductive work behavior (CWB), whereas some previous studies failed to find such a relationship. We tested occupational homogeneity of the sample and criterion measurement as two potential explanations for these inconsistencies. Study 1 replicated major design features of one previous study, which found no GMA–CWB relation in a heterogeneous sample, with occupationally homogeneous groups. Results confirmed previous null findings, indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Finally, there was a modest significant negative relation between GPA and CAB ( r = −.26, p < .01), indicating that GPA and CAB, although related, are sufficiently distinguishable criteria for the purposes of this study. This finding is in line with recent work that indicated a modest negative relation between GPA and counterproductive work behaviour (Marcus et al, 2009).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Finally, there was a modest significant negative relation between GPA and CAB ( r = −.26, p < .01), indicating that GPA and CAB, although related, are sufficiently distinguishable criteria for the purposes of this study. This finding is in line with recent work that indicated a modest negative relation between GPA and counterproductive work behaviour (Marcus et al, 2009).…”
Section: Resultssupporting
confidence: 93%
“…This last finding may be explained by the fact that conscientious students are organized, hard working, precise, and persistent—characteristics which appear to make counterproductive behaviours superfluous. Besides Conscientiousness, Honesty–Humility (comparable to Integrity) seems to be especially important in the prediction of counterproductive behaviours at work (Ashton & Lee, 2008; Lee, Ashton, & De Vries, 2005; Lee, Ashton, & Shin, 2005; Marcus, Wagner, Poole, Powell, & Carswell, 2009) and at school (Marcus et al, 2007). An explanation for this last finding may be that students who score high on Honesty–Humility are unwilling to take advantage of others and therefore avoid CAB.…”
Section: Introductionmentioning
confidence: 99%
“…The authors also find other indirect measures of cognitive ability, such as college grades or years of education, to correlate negatively, although mildly, to counterproductive work behaviors. Some studies have failed to report a negative relationship between intelligence measures and counterproductive work behaviors when using self-reported measures of counterproductive work behaviors [ 14 ][ 15 ][ 16 ][ 17 ]. The negative relationship between counterproductive work behaviors and intelligence may be due to the inhibitory effect of intelligence with regard to deviant behaviors as is conjectured by [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…While the dominant traits of intelligent females are innovation and responsibility, the dominant traits of males are risk taking and innovation. Such results may help in selecting the right candidates as many studies indicated that the most predictive variables of future performance of recent college graduates are personality and mental ability (Koczwara, 2012;Sjoberg et al, 2012;Marcus et al, 2009;Cook, 2009;Schmidt, Shaffer, & OH, 2008;Rode et al, 2008;Schmidt & Hunter, 2004;Gottfredson, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Societies, companies, organization and academia emphasize the importance of intelligence in order to keep up with development in technology and fast learning societies (Gottfredson, 1997). Research has indicated that fresh graduates with high mental abilities are more likely to leave better impressions during job interviews and show increased job performance in the future (Sjoberg et al, 2012;Marcus et al, 2009;Cook, 2009;Schmidt, Shaffer, & OH, 2008;Rode et al, 2008;Gerald, Witt, & Hochwarter, 2001;Livenes, Highhouse, & De Corte, 2005;Schmidt & Hunter, 2004;Gottfredson, 1997). Companies realize long ago that intelligent fresh graduates learn new tasks faster than low mental abilities graduates and make fewer mistakes (Salgado et al, 2003;Brand, 1987).…”
Section: Introductionmentioning
confidence: 99%